Variations in Pu isotopic composition in soils from the Spitsbergen (Norway): Three potential pollution sources of the Arctic region. (July 2017) - Łokas, E.; Anczkiewicz, R.; Kierepko, R.; Mietelski, J.W.
Abstract: Although the polar regions have not been industrialised, numerous contaminants originating from human activity are detectable in the Arctic environment. This study reports evidence of 240 Pu/ 239 Pu atomic ratios in the tundra and initial soils from different parts of west and central Spitsbergen and recognizes possible environmental inputs of non-global fallout Pu. The average atomic ratio of 240 Pu/ 239 Pu equal to 0.179 (ranging between 0.129 and 0.201) in tundra soils are comparable to the characteristic ratio for global fallout (0.180). However, the 240 Pu/ 239 Pu atomic ratios in the initial soils from proglacial zone of glaciers change within wide range between 0.1281 and 0.234 with the mean value of 0.169. By combining alpha and mass spectrometry, the three-sources model was used to identify the Pu sources in initial soils. Our study indicated that the main source of Pu is nuclear tests and that a second source with lower Pu ratio may come from weapons grade Pu (unexploded weapons grade Pu ie. material from bomb which didn't undergo nuclear explosions for example for security tests). Additionally, we found samples with high 238 Pu/ 239+240 Pu activity ratios and with typical global fallout 240 Pu/ 239 Pu atomic ratios, which are associated with separate sources of pure 238 Pu from the SNAP-9A satellite burn up in the atmosphere. Highlights: Quantification of 240 Pu/ 239 Pu atomic ratios in Arctic soils. Stronger radioactive contamination in the Arctic proglacial zone of glaciers than in tundra. Identification of Pu sources using three-sources model. Excess of 238 Pu suggests a separate source of 238 Pu contamination.